2024
DOI: 10.1007/s00784-024-05514-8
|View full text |Cite
|
Sign up to set email alerts
|

Occult metastasis is no burden factor in oral squamous cell carcinoma patients when adhering to a standardized approach in neck dissection

Ann-Kristin Struckmeier,
Mayte Buchbender,
Tobias Moest
et al.

Abstract: Objectives Management of the neck in patients with oral squamous cell carcinoma (OSCC) is pivotal to oncologic control and survival. However, there is controversy regarding necessity of neck dissection (ND) in patients with clinically node-negative neck. We aimed to assess risk factors for occult metastasis and to explore whether the presence of occult lymph node metastases (LNMs) has an impact on recurrence and survival. Material and methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The incidence of OM is reported to be 7-33.75% in cN0 OSCC [7][8][9][10][11][12]. This study observed OM in 9 (10.5%) of the 86 patients, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The incidence of OM is reported to be 7-33.75% in cN0 OSCC [7][8][9][10][11][12]. This study observed OM in 9 (10.5%) of the 86 patients, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…The indication of END for a cN0 neck is controversial. Some investigators reported that END could prevent regional recurrence [9,12], while others considered END an aggressive treatment because of shoulder dysfunction and aesthetic side effects [29,30], and the observation policy is considered reasonable for appropriately selected patients who can undergo very close follow-ups [4,5]. In this study, we applied END to patients with reconstructive surgery, a tumor depth ≥ 4 mm in tongue cancer, and more than a segmental resection of the mandible performed when a cervical approach was required for primary resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations